The Effect of the Number of Blades on the Efficiency of A Wind Turbine. Issue 1 (June 2021) - Adeyeye, Kehinde Adeseye; Ijumba, Nelson; Colton, Jonathan
Abstract: In this paper, we examine existing literature on the way that the number of blades of a wind turbine affects its efficiency and power generation. A wind turbine blade is an important component of a clean energy system because of its ability to capture energy from the wind. The power that a wind turbine extracts from the wind is directly proportional to the swept area of the blades; consequently, the blades have a direct effect on power generation. The number and configuration of the blades is very important because it affects the speed and efficiency of turbine. Unfortunately, as the number of blades increases, so does the slipstream effect. Too few a number of blades results in poor efficiency and thus inadequate performance. Too large a number of blades increases weight and production cost. The correct number of blades is important to fit the generator performance curve to optimize overall turbine performance and efficiency.